Isolation and Biological Control of Colletotrichum sp. Causing Anthracnosis in Theobroma cacao L. in Chiapas, Mexico - Nadia Denisse Rodríguez-Velázquez; Irene Gómez-de la Cruz; Guillermo López-Guillen; Belén Chávez-Ramírez; Paulina Estrada-de los Santos (Journal of Fungi)
Anthracnose is a phytosanitary issue caused by various species of Colletotrichum. This study aims to revise the presence of Colletotrichum in the south of Mexico (the Soconusco area in Chiapas) and assess the inhibitory capacity of Paenibacillus sp. NMA1017 against Colletotrichum in in vitro and field experiments. The study involved sampling pods with anthracnose from 17 sites in the Soconusco area, Chiapas, Mexico. The incidence of the disease ranged from 0.6 to 11.63%. A total of 142 isolates exhibiting the morphological characteristics of the Colletotrichum genus were obtained. Fifty selected isolates were identified using the ITS region and were classified as Colletotrichum gloeosporioides with 99% similarity. The concatenation of morphological and physiological characteristics resulted in nine main clusters. The in vitro test showed that Paenibacillus sp. NMA1017 inhibited the fungal growth of selected strains by 30–50%. The field experiments included three commercial biocontrol agents, Paenibacillus sp. NMA1017, and a water control. The incidence of anthracnose (control with water) ranged from 32 to 65%, while the commercial biocontrol agents and Paenibacillus showed an incidence range of 12 to 20%. These findings support the use of Paenibacillus sp. NMA1017 as a biocontrol agent for cacao anthracnose.